Situs memori sebagai representasi: Filsafat Jawa dan nilai pendidikan karakter dalam Film Ziarah (2017) - Yatun Romdonah Awaliah; Sutrisna Wibawa (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
The film is a product of a popular culture that represents and constructs the life of a society. This mimetic view implies the position of the film as a recording or reflection of social reality. Ziarah (2017) is a drama genre film that tells the story of Mbah Sri, a 95-year-old woman looking for her husband because he doesn't come home and she doesn't hear from him after saying goodbye to the Military Aggression II war in 1948. This film is wholly based on the plot of Mbah Sri's story as heir to the memory of the historical events experienced by her husband. This tendency represents Mbah Sri's view of Javanese philosophy and the value of character education that he believes in. This research uses a qualitative method with a descriptive type through Paul Ricoeur's hermeneutic analysis technique. The results of the study are presented as follows. First, the film Ziarah (2017) articulates the philosophy of sangkan paran ning dumadi (where he came from and where to return) as a belief in the temporary position of humans on earth through the projection of Mbah Sri's journey while looking for her late husband. Second, the film Ziarah (2017) emphasizes the event of Military Aggression II in 1948 as a social-collective memory so that the values ​​of nationalism and patriotism are also contained. Third, character education reflected in the film Ziarah (2017) is dominated by the process of imitating the character of national leaders, historical figures, and the culture of an area.